Analisis Kinerja Operasional Pola Pengeboran Wedge Cut: Studi Kasus Waktu Edar dan Efisiensi Bahan Peledak di PT Malea Energy - Syamsuddin; Hendra Sani (Fakultas Teknik UPRI, 2024)
Efficient drilling and blasting operations are critical for optimizing productivity in surface mining.This study investigates the actual drilling cycle time and explosive application parameters in PT MaleaEnergy, which applies a Wedge Cut (V-Cut) pattern. Field data were collected on drilling time, rodlifting, positioning, and the use of Power Gel explosives and delay detonators. The actual drillingpenetration rate was 1.41 m/min with an effective working time of 520 minutes per shift. A total of 15explosive cartridges per hole and delay times between 0–3500 ms were applied. Results indicate thatdrilling efficiency is significantly influenced not only by cycle time management but also by explosivedelay configuration. This study provides a quantitative evaluation that bridges the gap between fieldoperation parameters and theoretical efficiency models. The findings are valuable for improving drill-blast design and time utilization in mid-scale mining operations